6(x+1)^2+2(x-1)(x^2+x+1)-2(x+1)^3=32 tìm x

Question

6(x+1)^2+2(x-1)(x^2+x+1)-2(x+1)^3=32 tìm x

in progress 0
Arya 3 tuần 2021-07-11T14:00:23+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-07-11T14:01:24+00:00

    Đáp án:

     $x=5$

    Giải thích các bước giải:

     $6.(x+1)^2+2.(x-1).(x^2+x+1)-2.(x+1)^3=32$

    $⇔6.(x^2+2x+1)+2.(x^3-1)-2.(x^3+3x^2+3x+1)=32$

    $⇔6x^2+12x+6+2x^3-2-2x^3-6x^2-6x-2=32$

    $⇔6x+2=32$

    $⇔6x=30$

    $⇔x=5$

    0
    2021-07-11T14:01:36+00:00

    Đây ạ

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )